VD_FINDINFO AP / 2011 / 73 vom 18. Mai 2010 - VD Tribunal cantonal (2010)
PRESCRIPTION, GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE, ABUS DE DROIT | 2 al. 2 CC, 135 ch. 1 CO, 135 ch. 2 CO, 371 al. 1 CO